A composite additive suitable for electrolyte and application thereof

CN117254107BActive Publication Date: 2026-10-09TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311233419.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2026-10-09
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

但是有机电解质一方面热稳定性差,在电池工作电压过高时,会发生电解质的分解或者化学反应;另一方面有机电解质能与正极活性材料之间充分接触,也会导致正极活性材料与电解质发生副反应,从而不利于电池的容量发挥

Benefits of technology

(1)本发明的复合添加剂能在正极活性物质的表面形成一层类CEI膜,不仅能隔绝电解质和正极活性物质之间的副反应,有利于提升电池的容量发挥;并且本发明的复合添加剂用于高工作电压的电池中,有利于电池保持较好的容量保持率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117254107B_ABST
    Figure CN117254107B_ABST
Patent Text Reader

Abstract

The application discloses a composite additive suitable for an electrolyte, the composite additive comprising aniline with a branched alkyl substituent and at least one ionic liquid, the ionic liquid being an ionic liquid with general formula (1-1) or general formula (1-2): the total mass proportion of the ionic liquid and the aniline with the branched alkyl substituent in the total mass of raw materials of the electrolyte is greater than 0.1% and less than 15%. The composite additive of the application can form a CEI-like film on the surface of the positive active material, not only can isolate the side reaction between the electrolyte and the positive active material, but also is beneficial to improve the capacity of the battery. The electrolyte of the application is used in a battery with high working voltage, which is beneficial to keep a good capacity retention rate of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and more specifically to a composite additive suitable for electrolytes and its application. Background Technology

[0002] Electrolytes are one of the core materials for the capacity of both primary and secondary batteries, and they act as a medium to improve the fluidity between the moving anode and cathode. As an important component of the battery, the electrolyte plays a crucial role in transporting ions and conducting current between the positive and negative electrodes. Selecting a suitable electrolyte is also key to obtaining secondary batteries with high energy density and power density, long cycle life, and good safety performance.

[0003] Organic electrolytes possess high chemical stability and durability; they also have low viscosity, allowing for ample contact with the positive electrode active material. This lower viscosity further facilitates ion transport within the battery and maintains high ionic conductivity at low temperatures. These advantages have led to their widespread use in batteries. However, organic electrolytes also suffer from poor thermal stability, leading to decomposition or chemical reactions at excessively high battery operating voltages. Furthermore, their close contact with the positive electrode active material can also cause side reactions, negatively impacting battery capacity. These factors limit the application of organic electrolytes in batteries. Summary of the Invention

[0004] This invention addresses the problems in the prior art by disclosing a composite additive suitable for electrolytes. The additive of this invention can reduce side reactions between the positive electrode active material and the electrolyte, which is beneficial to improving the capacity of the battery. Furthermore, when the composite additive of this invention is used in batteries with high operating voltage, it helps the battery maintain a good capacity retention rate.

[0005] This invention is achieved through the following technical solution: This invention provides a composite additive suitable for electrolytes, the composite additive comprising aniline having branched hydrocarbon substituent groups and at least one ionic liquid, wherein the ionic liquid is an ionic liquid having general formula (1-1) or general formula (1-2): General formula (1-1) General formula (1-2) Wherein, R1 is selected from one of substituted or unsubstituted phenyl or fused-ring aryl groups, and the substituent of the substituted phenyl or fused-ring aryl group is selected from one or more of halogen, amino, hydroxy, and cyano groups; R2 is selected from one of substituted or unsubstituted hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group, and the substituent of the substituted hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group is selected from one or more of halogen, amino, hydroxy, and cyano groups; n is 1-10, and n is an integer; X - It is selected from one or more of the following: halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, and acetate ions.

[0006] In the above-described design of this invention, aniline can undergo self-polymerization to form a CEI-like film coating the surface of the positive electrode active material, thereby isolating the contact between the electrolyte and the positive electrode active material and improving the battery's capacity. Furthermore, the combination of the benzene ring in aniline and the R1 substituent group in the ionic liquid enhances the electrochemical window of the electrolyte, thus improving its antioxidant capacity. We further designed aniline and the ionic liquid to form an ion transport channel, further improving the battery's ion conductivity. The amino nitrogen in aniline is electronegative; due to the lone pair electrons of nitrogen and the effect of the amino group, the charge of the benzene ring redistributes. Furthermore, branched hydrocarbon substituent groups are designed on aniline. The combined selection of the amino group and the branched hydrocarbon substituent groups makes the branched hydrocarbon substituent groups more suitable for faster electrophilic substitution reactions with the ortho and meta positions of the amino group, thus contributing to the structural stability of aniline with branched hydrocarbon substituent groups. To facilitate the interaction between ionic liquids and aniline, we designed R1 substituents on the ionic liquid. These branched hydrocarbon substituents not only enhance the structural stability of aniline but also promote a stable π-π conjugation effect between the benzene ring in aniline and the R1 substituent, thus fostering stable ion transport channels between aniline and the ionic liquid. Furthermore, the branched hydrocarbon substituents reduce the rigidity of the aniline backbone, decreasing inter-chain forces and allowing imidazole or pyridine groups in the ionic liquid to align uniformly along the polyaniline backbone. This results in stable ion transport channels both between and on the backbone, improving the battery's ionic conductivity and performance. Building upon this, we also designed R2 substituents on the ionic liquid, which, while promoting backbone creep, also contributes to the formation of even more abundant ion conduction channels.

[0007] Further preferably, the mass ratio of the ionic liquid to the aniline with branched hydrocarbon substituents in the composite additive is 0.2-2 parts: 0.1-5 parts.

[0008] Further preferably, the mass ratio of the ionic liquid to the aniline with branched hydrocarbon substituents in the composite additive is 0.4-0.6 parts: 0.15-0.25 parts. This not only provides good ionic conductivity but also enhances the stability of the electrolyte.

[0009] As a further embodiment, the aniline having branched hydrocarbon substituents is an aniline having general formula (2-1) and / or having general formula (2-2); General formula (2-1) General formula (2-2) R3 and R4 are each independently selected from one of the following: substituted or unsubstituted C1-C20 hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group. The substituents of the substituted C1-C20 hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group are selected from one or more of halogen, amino, hydroxyl, and cyano groups.

[0010] As a further embodiment, R1 is selected from one of substituted or unsubstituted phenyl, naphthyl, or anthracene groups, and the substituents of the substituted phenyl, naphthyl, or anthracene groups are selected from one or more of halogen, amino, hydroxyl, and cyano groups. In addition to forming a π-π conjugation effect with the benzene ring in aniline, it also has relatively small steric hindrance, thus making the coordination between the ionic liquid and polyaniline more favorable.

[0011] As a further option, the halide ion includes F - ,Br - I - Cl - One or more of them.

[0012] As a further embodiment, the phosphate ions include fluorine-substituted or unsubstituted phosphate ions.

[0013] As a further embodiment, the fluorine-substituted phosphate ions include PF6. - (Hexafluorophosphate ion).

[0014] As a further option, the perchlorate ion includes ClO4. - (Perchlorate ion).

[0015] As a further embodiment, the sulfonamide ion includes one or more of fluorine-substituted or unsubstituted sulfonamide ions.

[0016] As a further embodiment, the fluorine-substituted sulfonamide ion includes TFSI. - (trifluoromethanesulfonylimide ion), FSI - One or more of (bis(fluorosulfonyl)imide ions).

[0017] As a further embodiment, the oxalate borate ion includes one or more of fluorine-substituted or unsubstituted oxalate borate ions.

[0018] As a further embodiment, the fluorine-substituted oxalate-borate ion includes DFOB. - (Difluorooxalate borate ion).

[0019] As a further option, R1 is phenyl. When R1 is phenyl, it has less steric hindrance, which is more conducive to the formation of a uniform arrangement on the main chain formed on aniline, thereby forming a better ion transport channel and improving the electrical performance of the battery.

[0020] As a further option, n is 1, 2, 3, 4, or 5. A shorter chain length is beneficial to the stability of the imidazole or pyridine groups and the R1 substituents in the ionic liquid, thereby facilitating the formation of stable ion transport channels between the main chains.

[0021] As a further embodiment, R2 is selected from one of substituted or unsubstituted C1-C10 hydrocarbon groups, and the substituents of the substituted C1-C10 hydrocarbon groups are selected from one or more of halogen, amino, hydroxyl, and cyano groups. Hydrocarbon groups can reduce intermolecular forces, thereby facilitating the formation of uniform ion transport channels between the ionic liquid and polyaniline.

[0022] As a further option, the halogen includes F - ,Br - I - Cl - One or more of them.

[0023] As a further refinement, R2 is selected from one of the unsubstituted C1-C5 hydrocarbon groups. Shorter chain lengths result in less peristalsis, reducing entanglement between molecular chains.

[0024] As a further option, R2 is a methyl group. When it is a methyl group, it has minimal steric hindrance and minimal entanglement between molecular chains.

[0025] As a further embodiment, R3 and R4 are each independently one of substituted or unsubstituted C1-C10 hydrocarbon groups, and the substituents of the substituted C1-C10 hydrocarbon groups are selected from halogens.

[0026] As a further refinement, R3 and R4 are each independently a C1-C5 hydrocarbon substituent group. With a smaller free volume, less molecular chain entanglement, and weaker steric hindrance, the polyaniline obtained by electropolymerization exhibits better coating properties for the positive electrode active material.

[0027] As a further refinement, R3 and R4 are each independently a methyl group. Methyl groups have the smallest free volume, resulting in optimal coating of the positive electrode active material.

[0028] The present invention also provides a polymer film formed by the composite additive.

[0029] The present invention also provides a battery electrode coated with an in-situ polymerized composite additive, wherein the battery electrode is polymerized on the surface of the electrode to form a polymer film, or the surface of the electrode has a polymer film formed by the composite additive.

[0030] As a further option, the thickness of the polymer film is 0.5 nm-3 μm. A thin film cannot uniformly coat the cathode material, while an excessively thick film affects the cathode reaction kinetics and reduces battery capacity.

[0031] As a further improvement, the thickness of the polymer film is 0.85μm-2μm.

[0032] As a further embodiment, the polymer film has at least one of the following characteristics: a. The room temperature ionic conductivity of the polymer membrane is 4 mS / cm-6.5 mS / cm; b. The electrochemical window of the polymer film is greater than 4.6V.

[0033] This invention also provides a method for preparing a battery electrode coated with an in-situ polymerized composite additive, the method comprising: Under a dry gas atmosphere, the composite additive is added to the electrolyte and mixed evenly. The battery electrode assembly is then assembled, and the evenly mixed electrolyte is injected. After sealing, the battery is left to stand for further processing and undergoes formation treatment. The composite additive is uniformly polymerized and coated on the surface of the electrode to form the battery electrode.

[0034] As a further embodiment, the formation process includes at least one constant current charging stage or a constant voltage charging stage. As a further improvement, the charging current density during the constant current charging phase is 0.1 mA / cm². 2 -20mA / cm 2 As a further embodiment, the charging voltage during the constant voltage charging phase is any voltage value within the voltage range defined by the lower limit and upper limit of the battery charging voltage. In this invention, the upper limit of the charging voltage is the maximum allowable charging voltage.

[0035] In the method of this invention, those skilled in the art can set the charging voltage of the corresponding constant voltage charging stage according to different battery systems. As an example, for instance, a lithium cobalt oxide battery uses lithium metal as a reference electrode. The voltage range of the constant voltage charging stage of the lithium cobalt oxide battery is 3.0-4.6V, and the charging voltage of the constant voltage charging stage can be any value within the range of 3.0-4.6V, such as 3.0V, 3.2V, 3.4V, 3.6V, 3.8V, 4.0V, 4.2V, 4.4V, 4.6V, etc., with an upper limit of 4.6V. For example, lithium iron phosphate batteries use lithium metal as the reference electrode. The voltage range for the constant voltage charging phase of a lithium iron phosphate battery is 3.0-3.65V, and the charging voltage during this phase can be any value within the 3.0-3.65V range, such as 3.0V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, 3.6V, or 3.65V, with an upper limit of 3.65V. In contrast, sodium-ion batteries use sodium metal as the reference electrode, and the voltage range for the constant voltage charging phase is 2.0-3.8V, with an upper limit of 3.8V.

[0036] As a further embodiment, the charging voltage during the constant voltage charging phase is 75%-90% of the upper limit of the charging voltage during the constant voltage charging phase. For the aforementioned lithium cobalt oxide battery, its upper limit of charging voltage is 4.6V, and according to calculations, its upper limit of charging voltage is 3.45-4.14V; for the lithium iron phosphate battery, its upper limit of charging voltage is 3.65V, and according to calculations, its upper limit of charging voltage is 2.73-3.28V; for the sodium-ion battery, its upper limit of charging voltage is 3.8V, and according to calculations, its upper limit of charging voltage is 2.85-3.42V.

[0037] As a further option, the gas is air or an inert gas.

[0038] As a further embodiment, the total mass of the ionic liquid and aniline with branched hydrocarbon substituents in the composite additive accounts for more than 0.1% and less than 15% of the total mass of the electrolyte.

[0039] As a further embodiment, the total mass of the ionic liquid in the composite additive accounts for 0.2%-2% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.1%-5% of the total mass of the electrolyte.

[0040] As a further improvement, the total mass of the ionic liquid in the composite additive accounts for 0.4%-0.6% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.15%-0.25% of the total mass of the electrolyte. This provides optimal coating of the positive electrode active material, reduces side reactions with the electrolyte, and generates a suitable amount of ion transport channels.

[0041] As a further embodiment, the electrolyte also includes salt, solvent, and other additives, wherein the ratio of salt, solvent, and other additives by mass is (10-50 parts):(50-70 parts):(0-10 parts).

[0042] As a further embodiment, the salt includes one or more of ABx, where ABx can dissociate cations and anions when used as an electrolyte. Here, A is selected from lithium ions, sodium ions, potassium ions, magnesium ions, aluminum ions, and zinc ions, and B is selected from anions of chloride salts, boron salts, arsenic salts, phosphorus salts, sulfonic acid salts, sulfonylimide salts, and aluminum salts. The value of x is determined based on the charge balance between A and B in the salt.

[0043] As a further embodiment, the anion of the chloride salt includes ClO4. - .

[0044] As a further embodiment, the boron-based salt includes a borate, wherein the anion in the borate includes tetrafluoroborate ions (BF4). - ), difluorooxalate borate ions (DFOB) - ), bis(oxalate)borate ion (BOB) - One or more of the following.

[0045] As a further embodiment, the anion in the arsenic-based salt includes hexafluoroarsenate ions (AsF6). - ).

[0046] As a further embodiment, the anion in the phosphate salt includes hexafluorophosphate (PF6) ions. - ), tri(pentafluoroethyl)trifluorophosphate ion [(C2F5)3PF3 - One or more of the following.

[0047] As a further embodiment, the anion in the sulfonic acid salt includes trifluoromethanesulfonate ions (CF3SO3). - ).

[0048] As a further embodiment, the anion in the sulfonyl imide salt includes a bis(fluorosulfonyl)imide ion (FSI). - ), bis(trifluoromethanesulfonyl)imide ion (TFSI) -), fluorosulfonyl-(trifluoromethanesulfonyl)imide ion (FTFSI) - ), bis(perfluoro-ethylsulfonyl)imine ion (BETI - One or more of them.

[0049] As a further embodiment, the anion in the aluminum-based salt includes tetrachloroaluminate ions (AlCl4). - ), tetrafluoroaluminate ions (AlF4) - One or more of the following.

[0050] As a further embodiment, the solvent includes one or more of ethylene carbonate, diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, propylene carbonate, dimethoxyethyl ether, dioxolane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether.

[0051] As a further option, the other additives include one or more of vinylene carbonate, fluoroethylene carbonate, and lithium nitrate.

[0052] The present invention also provides electrolytes, batteries or electrochemical devices having the aforementioned composite additives.

[0053] As a further embodiment, the total mass of the ionic liquid and aniline with branched hydrocarbon substituents in the composite additive accounts for more than 0.1% and less than 15% of the total mass of the electrolyte.

[0054] As a further embodiment, the total mass of the ionic liquid in the composite additive accounts for 0.2%-2% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.1%-5% of the total mass of the electrolyte.

[0055] As a further improvement, the total mass of the ionic liquid in the composite additive accounts for 0.4%-0.6% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.15%-0.25% of the total mass of the electrolyte. This provides optimal coating of the positive electrode active material, reduces side reactions with the electrolyte, and generates a suitable amount of ion transport channels.

[0056] As a further embodiment, the electrolyte also includes salt, solvent, and other additives, wherein the ratio of salt, solvent, and other additives by mass is (10-50 parts):(50-70 parts):(0-10 parts).

[0057] As a further embodiment, the battery also includes a positive electrode, a negative electrode, and a separator.

[0058] As a further embodiment, the positive electrode includes a positive electrode active material, a conductive agent, and a binder.

[0059] As a further embodiment, the positive electrode active material includes one or more of the following: lithium battery positive electrode active material, sodium battery positive electrode active material, magnesium battery positive electrode active material, aluminum battery positive electrode active material, and zinc battery positive electrode active material.

[0060] As a further embodiment, the positive electrode active material of the lithium battery includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel oxide, lithium iron phosphate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, or nickel cobalt manganese aluminum quaternary material.

[0061] As a further embodiment, the active material of the sodium battery cathode includes one or more of P2 crystalline oxide and O3 crystalline oxide.

[0062] As a further embodiment, the P2 crystalline oxide includes Na x MO2, where x is in the range of 0.5≤x≤0.8, and M is selected from one or more of Co, Mn, Fe, Ni, Ti, Cr, V, and Cu.

[0063] As a further embodiment, the O3 crystalline oxide includes Na y MO2, where y is in the range of 0.8≤y≤1, and M is selected from one or more of Co, Mn, Fe, Ni, Ti, Cr, V, Cu, and Sb.

[0064] As a further improvement, the positive electrode active material of the magnesium battery includes magnesium oxide.

[0065] As a further improvement, the positive electrode active material of the aluminum battery includes one or more of Prussian blue and Prussian white.

[0066] As a further improvement, the positive electrode active material of the zinc battery includes manganese dioxide.

[0067] Those skilled in the art should understand that different battery systems correspond to different positive electrode active materials and salts. Therefore, in this invention, the appropriate positive electrode active materials and salts can be selected according to the chosen battery system.

[0068] As a further embodiment, the negative electrode includes a negative electrode active material, a conductive agent, and a binder.

[0069] As a further embodiment, the negative electrode active material includes one or more of carbon materials, silicon-carbon composites, silicon, metals, and alloy compounds.

[0070] As a further embodiment, the carbon material includes one or more of graphite, hard carbon, graphene, carbon nanotubes, carbon nanofibers, natural graphite, artificial graphite, and carbon black.

[0071] As a further embodiment, the metal includes one of lithium, aluminum, sodium, magnesium, and zinc.

[0072] As a further embodiment, the battery can be used in 3C products, including but not limited to computers, tablets, mice, mobile phones, digital cameras, Walkmans, electronic dictionaries, digital audio players, smartwatches, MP3 players, MP4 players, radios, and Bluetooth headsets.

[0073] As a further embodiment, the electrochemical device can be used in end-consumer products, including but not limited to mobile phones, laptops, pen input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, and portable printers.

[0074] As a further embodiment, the electrochemical device can be used in electrical equipment, including large and small electrical equipment. Small electrical equipment includes consumer products, wearable electronic devices, or portable electronic devices; large electrical equipment includes transportation equipment. Transportation equipment includes, but is not limited to, vehicles such as automobiles, motorcycles, electric bicycles, buses, subways, high-speed trains, airplanes, and ships. Wearable electronic devices or portable electronic devices include, but are not limited to, headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, drones, motors, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors. The electrolyte of this invention is used in an electrochemical device, which can be housed in the form of an electrochemical device within an electrical device. Typically, this electrochemical device includes a battery pack or / and multiple battery modules or / and a single battery module or / and a management system for controlling them.

[0075] The features and beneficial effects of this invention are as follows: (1) The composite additive of the present invention can form a CEI-like film on the surface of the positive electrode active material, which can not only isolate the side reaction between the electrolyte and the positive electrode active material, but also improve the capacity of the battery; and the composite additive of the present invention is used in batteries with high working voltage, which is conducive to the battery maintaining a good capacity retention rate.

[0076] (2) The ionic liquid in this invention forms a π-π conjugation effect in the electrolyte after polymerization of aniline with branched hydrocarbon substituent groups. The ionic liquid is evenly distributed along the main chain of polyaniline, thereby improving the ionic conductivity between polyaniline itself and the main chain, which is beneficial to improving the ionic conductivity of the battery.

[0077] (3) The electrolyte with the composite additive of the present invention can be used in lithium cobalt oxide batteries, and the working voltage of lithium cobalt oxide is not lower than 4.3V. The electrolyte of the present invention exists stably in lithium cobalt oxide batteries, and the composite additive of the electrolyte of the present invention can form a coating layer on the surface of lithium cobalt oxide particles, which isolates the side reaction between lithium cobalt oxide and electrolyte. The capacity retention rate of the lithium cobalt oxide battery of the present invention is higher than 70% and the third discharge specific capacity is higher than 175mAh / g. Attached Figure Description

[0078] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0079] Figure 1 The results are the capacity retention rate test results of an embodiment of the present invention.

[0080] Figure 2 The present invention provides methods for preparing ionic liquids in Examples 1-7 and Example 10.

[0081] Figure 3 This is the preparation method of the ionic liquid in Example 8 of the present invention.

[0082] Figure 4 This is the preparation method of the ionic liquid in Example 9 of the present invention.

[0083] Figure 5 This is the preparation method of ionic liquid in Example 11 of the present invention.

[0084] Figure 6 This is the preparation method of ionic liquid in Example 12 of the present invention.

[0085] Figure 7 The relative positions between the ionic liquid and the polyaniline formed after polymerization of aniline in the embodiments of the present invention are shown.

[0086] Figure 8 This is a schematic diagram of the self-polymerization of aniline in this invention. Detailed Implementation

[0087] To facilitate understanding of the composite additive of the present invention, a more comprehensive description of the composite additive of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.

[0088] Using the composite additives of this invention in the electrolyte is beneficial to improving the electrical performance of the battery. This invention primarily uses a lithium battery as an example, applying the obtained electrolyte to a lithium battery to further illustrate the synergistic effect of the composite additives in the electrolyte on the final improved electrical performance of the battery. The composite additives obtained by this invention are not limited to lithium batteries; they can also be used in sodium batteries, potassium batteries, etc.

[0089] Example 1

[0090] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the solution was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) was added and stirred for 1h. The solution was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid. Figure 2 As shown.

[0091] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 (lithium hexafluorophosphate), with a mass ratio of EC (ethylene carbonate):EMC (ethyl methyl carbonate):DMC (dimethyl carbonate) of 1:1:1. 2-Isopropylaniline accounts for 0.1 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.2 wt% of the total mass of the electrolyte raw materials.

[0092] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0093] Example 2

[0094] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0095] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.2 wt% of the total mass of the electrolyte raw materials.

[0096] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0097] Example 3

[0098] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0099] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.5 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.2 wt% of the total mass of the electrolyte raw materials.

[0100] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0101] Example 4

[0102] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0103] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 1 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.2 wt% of the total mass of the electrolyte raw materials.

[0104] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0105] Example 5

[0106] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0107] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0108] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0109] Example 6

[0110] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0111] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 1 wt% of the total mass of the electrolyte raw materials.

[0112] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0113] Example 7

[0114] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0115] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 2 wt% of the total mass of the electrolyte raw materials.

[0116] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0117] Example 8

[0118] (1) Preparation of ionic liquids with benzene ring groups 50 g of 4-phenyl-1-butyl bromide and 23 g of N-methylimidazole were dissolved in 50 mL of ethyl acetate solution. The mixture was heated and stirred at 70 °C for 24 h. After stirring, the solution was separated into three layers using 50 mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 60 g (87% yield) of a reddish-brown liquid. 50 g of the reddish-brown liquid was dissolved in 50 g of deionized water. 29 g of LiDFOB (lithium difluorooxalate borate) was added and stirred for 1 h. The solution was then separated into three layers using 50 mL of deionized water. The lower layer was freeze-dried to obtain 57 g (95% yield) of a reddish-brown liquid. Figure 3 As shown.

[0119] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0120] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0121] Example 9

[0122] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 60g of 1-n-butylimidazolium were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the solution was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 82g (82% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 45g of LiFSI (lithium bis(fluorosulfonyl)imide) was added and stirred for 1h. The solution was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 72g (91% yield) of a reddish-brown liquid. Figure 4 As shown.

[0123] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0124] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0125] Example 10

[0126] (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the solution was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) was added and stirred for 1h. The solution was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid. Figure 5 As shown.

[0127] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6EC:EMC:DMC in a mass ratio of 1:1:1. 2-sec-butylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0128] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0129] Example 11

[0130] (1) Preparation of ionic liquids with naphthyl groups 50 g of 1-(2-chloroethyl)naphthalene and 26 g of N-methylimidazolium were dissolved in 50 mL of ethyl acetate solution. The mixture was heated and stirred at 70 °C for 24 h. After stirring, the solution was separated into three layers using 50 mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 60 g (70% yield) of a reddish-brown liquid. 50 g of the reddish-brown liquid was dissolved in 50 g of deionized water. 40 g of LiFSI (lithium bis(trifluoromethanesulfonyl)imide) was added and stirred for 1 h. The solution was then separated into three layers using 50 mL of deionized water. The lower layer was freeze-dried to obtain 70 g (92% yield) of a reddish-brown liquid. Figure 6 As shown.

[0131] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-sec-butylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0132] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0133] Example 12

[0134] (1) Preparation of ionic liquids with anthracene groups 50 g of 9-chloromethylanthracene and 22 g of N-methylimidazole were dissolved in 50 mL of ethyl acetate solution. The mixture was heated and stirred at 70 °C for 24 h. After stirring, the solution was separated into three layers using 50 mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 55 g (81% yield) of a reddish-brown liquid. 50 g of the reddish-brown liquid was dissolved in 50 g of deionized water. 30 g of LiFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1 h. The solution was then separated into three layers using 50 mL of deionized water. The lower layer was freeze-dried to obtain 53 g (88% yield) of a reddish-brown liquid. Figure 7 As shown.

[0135] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-sec-butylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0136] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0137] Comparative Example 1 (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0138] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6EC:EMC:DMC in a mass ratio of 1:1:1, and the ionic liquid with benzene ring groups accounts for 0.5 wt% of the total mass of the electrolyte raw materials.

[0139] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0140] Comparative Example 2 (1) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1, and 2-isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials.

[0141] (2) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0142] Comparative Example 3 (1) Preparation of ionic liquids with benzene ring groups 50g of benzyl chloride and 40g of N-methylimidazole were dissolved in 50mL of ethyl acetate solution. The mixture was heated and stirred at 70℃ for 24h. After stirring, the mixture was separated into three layers using 50mL of ethyl acetate. The lower layer was distilled under reduced pressure to obtain 71g (85% yield) of a reddish-brown liquid. 50g of the reddish-brown liquid was dissolved in 50g of deionized water. 83g of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) was added and stirred for 1h. The mixture was then separated into three layers using 50mL of deionized water. The lower layer was freeze-dried to obtain 99g (90% yield) of a reddish-brown liquid.

[0143] (2) Preparation of electrolyte The basic electrolyte is 1M LiPF6 EC:EMC:DMC in a mass ratio of 1:1:1. 2-Propylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and ionic liquids with benzene ring groups account for 0.5 wt% of the total mass of the electrolyte raw materials.

[0144] (3) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) in a mass ratio of 8:1:1 as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were conducted at a 0.5C rate within a voltage range of 3V-4.6V.

[0145] Comparative Example 4 (1) Preparation of electrolyte The basic electrolyte is 1M LiPF6EC:EMC:DMC in a mass ratio of 1:1:1. 2-Isopropylaniline accounts for 0.2 wt% of the total mass of the electrolyte raw materials, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt accounts for 0.5 wt% of the total mass of the electrolyte raw materials.

[0146] (2) Battery assembly A coin cell battery was assembled using lithium cobalt oxide (LiCoO2), carbon black (SP), and polyvinylidene fluoride (HSV900) (mass ratio 8:1:1) as the positive electrode material, a 25μm thick PP separator, and lithium foil as the negative electrode. The formation process involved charging at a constant voltage of 3.8V for 24 hours. Constant current charge-discharge tests were then conducted at a 0.5C rate within a high voltage range of 3V-4.6V.

[0147] The thickness of the polymer layer was obtained by scanning electron microscopy analysis of the cross-section of the polymer-coated electrode.

[0148] The polymer layer ionic conductivity is obtained by preparing a polymer film, assembling a stainless steel-stainless steel symmetric cell, testing its impedance (R), and calculating it using the formula σ=d / (RS), where d is the polymer thickness and S is the effective area of ​​the polymer in the middle of the electrode.

[0149] Verification Result Analysis: Table 1. Electrical performance test results of embodiments and comparative examples of the present invention.

[0150] We used the composite additive of this invention in an electrolyte and then applied the electrolyte to a lithium cobalt oxide battery to further investigate its effect on battery electrical performance. We studied the characteristics of the composite additive of this invention through a series of examples and comparative examples, and the results are shown in Table 1 and... Figure 1 As shown in Table 1, the discharge specific capacity and capacity retention of the batteries in Examples 1-12 of this invention are superior to those in Comparative Examples 1-4. This demonstrates that the composite additive of this invention can significantly improve the electrical performance of the battery. We believe this is likely because the synergistic effect between the ionic liquid and aniline with branched hydrocarbon substituents not only reduces side reactions between the electrolyte and the positive electrode active material, thereby reducing the dissolution of transition metals in the positive electrode active material, which is beneficial for improving the discharge specific capacity and cycle performance of the battery, but also increases the ionic conductivity of the battery. Firstly, aniline with branched hydrocarbon substituents can undergo self-polymerization (e.g., ...). Figure 8As shown), a CEI-like film is formed and coated on the surface of the positive electrode active material. Branched hydrocarbon substituents are placed at the ortho or meta positions of the amino group in aniline. Due to the electronegativity of the amino nitrogen in aniline, the lone pair electrons of nitrogen and the effect of the amino group promote the redistribution of charge on the benzene ring. Therefore, the branched hydrocarbon substituents at the ortho and meta positions of aniline can improve the structural stability of aniline. R1 substituents are designed on the ionic liquid. The benzene ring in aniline and the R1 substituents form a π-π conjugation effect, promoting the formation of ion transport channels between aniline and the ionic liquid (e.g., ...). Figure 7 As shown in the diagram, the ionic liquid is uniformly arranged along the direction of the polyaniline backbone, and the branches attached to the benzene ring in the ionic liquid form uniform ion transport channels between the polyaniline backbone. The ionic liquid not only reduces the rigidity of the aniline backbone and decreases the intermolecular forces formed by the polymerization of aniline itself, thus facilitating the uniform arrangement of imidazole or pyridine groups in the ionic liquid along the polyaniline backbone, forming stable ion transport channels between and on the backbone, improving the battery's ionic conductivity and performance; it also promotes a stable π-π conjugation effect between the benzene ring and the R1 substituent group in aniline, promoting the formation of stable ion transport channels in the electrolyte. Furthermore, we found that the synergy between the R1 substituent group in the ionic liquid and aniline enhances the electrolyte's electrochemical window and antioxidant capacity. Finally, the design of R2 substituent groups on the ionic liquid further facilitates the formation of more abundant ion conduction channels in the electrolyte based on backbone peristalsis. Therefore, the present invention achieves improved battery electrical performance through the synergy between the ionic liquid and aniline with branched hydrocarbon substituent groups in the composite additive.

[0151] Building on this, we further investigated how the combination of ionic liquids and aniline with branched hydrocarbon substituents can further improve the electrical performance of the battery.

[0152] First, aniline undergoes self-polymerization, and an ionic liquid is used to form a coating layer with ion-conducting properties. The branched hydrocarbon substituents in aniline having general formula (2-1) or general formula (2-2) not only give aniline a stable structure and form a stable π-π conjugation effect, but also promote the coating effect of polyaniline on the positive electrode active material. We believe this is primarily because the branched substituents are less prone to entanglement, which is beneficial for better coating of the positive electrode active material by the polyaniline obtained through electropolymerization during battery formation. We can verify this by comparing Example 5 with Comparative Example 3, and find that Example 5 has a better discharge specific capacity. Secondly, when the molecular chains of R3 and R4 in the branched substituents are shorter, they are less prone to entanglement and have a weaker steric hindrance effect, thus further improving the coating effect on the positive electrode active material. Therefore, we further prefer that R3 and R4 in the aniline are each an independent C1-C5 hydrocarbon group. Further comparison of Examples 5 and 10 revealed that Example 5 exhibited a better discharge specific capacity than Example 10. We believe this is because when R3 and R4 are methyl groups, intermolecular entanglement is minimized, resulting in a more stable coating structure. Therefore, we further prefer that R3 and R4 in the aniline are each independently a methyl substituent group.

[0153] Building upon this, we further promoted the synergistic effect between the ionic liquid and aniline. The R1 substituent group in the ionic liquid can form a π-π conjugation effect with the benzene ring in aniline, resulting in a uniform arrangement of the ionic liquid and improving the ionic conductivity of the polyaniline obtained after aniline self-polymerization. Comparing Examples 10-12, we found that Example 10 achieved better cycle performance and discharge specific capacity. We believe this is because when R1 is phenyl, naphthyl, or anthracene, as the number of benzene rings increases, the volume of the ionic liquid with benzene ring groups increases, resulting in greater steric hindrance and making it more difficult to uniformly arrange on the polyaniline backbone, thus failing to form uniform ion transport channels and reducing battery performance. We further optimized the ionic liquid so that the R1 substituent group is phenyl.

[0154] Ionic liquids not only form ion transport channels on the main chain of polyaniline but also between the main chains. To promote the uniformity of ion transport channels between the main chains, we further designed the structure of the ionic liquid. Comparing Example 5 with Examples 8-9, we found that Example 8 is the optimal choice. We believe this is because constructing ion transport channels between the main chains requires that the molecular chains between the main chains meet certain lengths to facilitate channel formation; it also requires minimizing entanglement between the molecular chains. Therefore, the R1 substituent group in the ionic liquid has a certain distance from the imidazole or pyridine group, which facilitates the formation of ion transport channels between the main chains. Furthermore, the cooperation between the imidazole or pyridine group and the R1 substituent group reduces the degrees of freedom of the molecular chains between the main chains, thereby reducing entanglement and promoting the formation of uniform ion transport channels. Based on this, reducing the length of the R2 substituent group in the ionic liquid reduces entanglement between the molecules and molecular chains, thus forming uniform ion transport channels between the main chains, which is beneficial to the battery's cycle performance. Therefore, we further prefer that n of the ionic liquid is 1-5; and that R2 is selected from one of C1-C5 hydrocarbon groups. Comparing Example 5 and Example 9, we found that Example 5 exhibits better cycle performance. We believe this is because having methyl R2 is more conducive to reducing intermolecular entanglement, thereby facilitating lithium-ion transport during battery cycling and thus improving battery cycle performance. Therefore, we further prefer that R2 is methyl.

[0155] Building upon this, we further investigated the effect of the addition of ionic liquid and aniline on the battery's electrical performance. The results are shown in Examples 1-7.

[0156] We first investigated different amounts of aniline, as shown in Examples 1-4. Our comparison revealed that Example 2 exhibited better discharge specific capacity and cycle performance. We believe that the capacity retention rate of the lithium cobalt oxide battery after 200 cycles initially increases and then decreases with increasing concentration. As the aniline content increases, the electropolymerized CEI becomes increasingly dense, resulting in better coating of lithium cobalt oxide. However, with further increases in content, a significant amount of aniline fails to polymerize, affecting the stability of the electrolyte and consequently the battery. Therefore, we further optimized the aniline content to be 0.15%-0.25% of the total electrolyte mass.

[0157] As shown in Table 1, the polymer membrane of this invention has an ionic conductivity of not less than 4.7 mS / cm, indicating that the polymer membrane obtained by this invention has good ionic conductivity. Based on this, we further investigated the amount of ionic liquid added. Comparing Examples 2 and 5-7, Example 5 showed better electrical performance. We believe this may be because as the amount of ionic liquid with benzene ring groups increases, the polymer membrane has more ion transport channels, which is beneficial for lithium ion transport. However, with further increases in content, more ionic liquid with benzene ring groups will be free in the electrolyte, affecting the stability of the electrolyte and consequently the stability of the battery. Therefore, we further prefer that the mass of the ionic liquid accounts for 0.4%-0.6% of the total mass of the electrolyte.

[0158] When the amounts of aniline and ionic liquid added are more appropriate, the polymer membrane can achieve better performance. Based on Examples 1-7 above, we further optimize the composition by mass, finding that the mass ratio of the ionic liquid to the aniline with branched hydrocarbon substituents in the composite additive is 0.4-0.6 parts: 0.15-0.25 parts. This not only provides good ionic conductivity but also improves the stability of the electrolyte.

[0159] In summary, the test results used in the embodiments of this invention are from lithium cobalt oxide batteries. In the prior art, the actual charging cutoff voltage of lithium cobalt oxide has reached a high voltage of 4.3V or higher. In embodiments 1-12 of this invention, the operating voltage of the lithium cobalt oxide battery reached a high voltage of 4.6V, and the capacity retention rate of the lithium cobalt oxide battery in embodiments 1-12 remained above 70%, with a third-cycle discharge specific capacity above 175mAh / g. In contrast, the lithium cobalt oxide batteries in Comparative Examples 1-4, at an operating voltage of 4.6V, only achieved a maximum capacity retention rate of 60%. It is evident that at high operating voltages, the electrolytes in the prior art suffer from poor stability and side reactions between the electrolyte and the positive electrode active material, leading to a decrease in battery electrical performance. The electrolyte with the composite additive of this invention can be used in batteries with high operating voltages, and the composite additive of the electrolyte obtained by this invention can form a CEI-like film on the surface of the positive electrode active material, which not only isolates the side reactions between the electrolyte and the positive electrode active material but also helps to improve the battery's capacity utilization and capacity retention rate.

[0160] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A composite additive suitable for electrolytes, characterized in that, The composite additive comprises aniline having branched hydrocarbon substituents and at least one ionic liquid, wherein the ionic liquid is an ionic liquid having general formula (1-1) or general formula (1-2): General formula (1-1) General formula (1-2) Wherein, R1 is selected from one of substituted or unsubstituted phenyl or fused-ring aryl groups, and the substituent of the substituted phenyl or fused-ring aryl group is selected from one or more of halogen, amino, hydroxy, and cyano groups; R2 is selected from one of substituted or unsubstituted hydrocarbon group, C1-C20 alkoxy group, carboxyl group, ester group, C2-C20 heterocyclic group, and carbonate group, and the substituent of the substituted hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group is selected from one or more of halogen, amino, hydroxy, and cyano groups; n is 1-10, and n is an integer; X - It is selected from one or more of the following: halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, and acetate ions.

2. The composite additive according to claim 1, characterized in that, The aniline having branched hydrocarbon substituents is an aniline having general formula (2-1) and / or having general formula (2-2); General formula (2-1) General formula (2-2) R3 and R4 are each independently selected from one of the following: substituted or unsubstituted C1-C20 hydrocarbon group, C1-C20 alkoxy group, carboxyl group, ester group, C2-C20 heterocyclic group, and carbonate group. The substituents of the substituted C1-C20 hydrocarbon group, C1-C20 alkoxy group, C3-C20 cyclic hydrocarbon group, carboxyl group, ester group, C2-C20 heterocyclic group, aryl group, and carbonate group are selected from one or more of halogen, amino, hydroxyl, and cyano groups.

3. The composite additive according to claim 2, characterized in that, R3 and R4 are each independently one of substituted or unsubstituted C1-C10 hydrocarbon groups, and the substituents of the substituted C1-C10 hydrocarbon groups are selected from halogens.

4. The composite additive according to claim 2, characterized in that, R3 and R4 are each an unsubstituted C1-C5 hydrocarbon group.

5. The composite additive according to claim 2, characterized in that, R3 and R4 are each independently methyl.

6. The composite additive according to claim 1, characterized in that, By mass, the mass ratio of the ionic liquid to the aniline with branched hydrocarbon substituents in the composite additive is 0.2-2 parts: 0.1-5 parts.

7. The composite additive according to claim 1, characterized in that, By mass, the mass ratio of the ionic liquid to the aniline with branched hydrocarbon substituents in the composite additive is 0.4-0.6 parts: 0.15-0.25 parts.

8. The composite additive according to claim 1, characterized in that, R1 is selected from one of substituted or unsubstituted phenyl, naphthyl or anthracene, and the substituent of the substituted phenyl, naphthyl or anthracene is selected from one or more of halogen, amino, hydroxyl or cyano.

9. A composite additive according to claim 1, characterized in that, R1 is a phenyl group.

10. A composite additive according to claim 1, characterized in that, The n is 1, 2, 3, 4 or 5.

11. A composite additive according to claim 1, characterized in that, R2 is selected from one of substituted or unsubstituted C1-C10 hydrocarbon groups, and the substituents of the substituted C1-C10 hydrocarbon groups are selected from one or more of halogen, amino, hydroxyl, and cyano groups.

12. The composite additive according to claim 1, characterized in that, The R2 is selected from one of the unsubstituted C1-C5 hydrocarbon groups.

13. The composite additive according to claim 1, characterized in that, R2 is a methyl group.

14. The composite additive according to claim 1, characterized in that, The halogen includes F. - ,Br - I - Cl - One or more of them.

15. A composite additive according to claim 1, characterized in that, The phosphate ions include fluorine-substituted or unsubstituted phosphate ions; the perchlorate ions include ClO4. - The sulfonamide ion includes one or more of fluorine-substituted or unsubstituted sulfonamide ions; the oxalate-borate ion includes one or more of fluorine-substituted or unsubstituted oxalate-borate ions; the halide ion includes F... - ,Br - I - Cl - One or more of them.

16. A composite additive according to claim 15, characterized in that, The fluorine-substituted phosphate ions include PF6. - .

17. A composite additive according to claim 15, characterized in that, The fluorine-substituted sulfonylimide ion includes TFSI. - FSI - One or more of them.

18. A composite additive according to claim 15, characterized in that, The fluorinated oxalate borate ion includes DFOB. - .

19. A polymer film, characterized in that, The polymer film is formed by uniformly polymerizing and coating the electrode surface with the composite additive described in any one of claims 1-18 during a formation process.

20. A battery positive electrode sheet coated with a composite additive through in-situ polymerization, characterized in that, The positive electrode of the battery is formed by uniformly polymerizing and coating a polymer film on the surface of the positive electrode during the formation process using the composite additive described in any one of claims 1-18.

21. The battery positive electrode sheet according to claim 20, characterized in that, The thickness of the polymer film is 0.5 nm to 3 μm.

22. The battery positive electrode sheet according to claim 20, characterized in that, The thickness of the polymer film is 0.85μm-2μm.

23. The positive electrode of the battery according to claim 20, characterized in that, The polymer film has at least one of the following characteristics: a. The room temperature ionic conductivity of the polymer membrane is 4 mS / cm-6.5 mS / cm; b. The electrochemical window of the polymer film is greater than 4.6V.

24. The method for preparing the battery positive electrode sheet coated with the composite additive through in-situ polymerization as described in claim 20, characterized in that, The preparation method includes: Under a dry gas atmosphere, the composite additive is added to the electrolyte and mixed evenly. The battery electrode assembly is then assembled, and the evenly mixed electrolyte is injected. After sealing, the battery is left to stand for further processing and undergoes formation treatment. The composite additive is uniformly polymerized and coated on the surface of the positive electrode to form the positive electrode of the battery.

25. The preparation method according to claim 24, characterized in that, The formation process includes at least one constant current charging stage or a constant voltage charging stage.

26. The preparation method according to claim 25, characterized in that, The charging current density during the constant current charging phase is 0.1 mA / cm². 2 -20mA / cm 2 .

27. The preparation method according to claim 25, characterized in that, The charging voltage during the constant voltage charging phase is any voltage value within the voltage range formed by the lower limit and upper limit of the battery charging voltage.

28. The preparation method according to claim 27, characterized in that, The charging voltage during the constant voltage charging phase is 75%-90% of the upper limit of the battery charging voltage.

29. The preparation method according to claim 24, characterized in that, The total mass of the ionic liquid and aniline with branched hydrocarbon substituents in the composite additive accounts for more than 0.1% and less than 15% of the total mass of the electrolyte.

30. The preparation method according to claim 24, characterized in that, The total mass of the ionic liquid in the composite additive accounts for 0.2%-2% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.1%-5% of the total mass of the electrolyte.

31. The preparation method according to claim 24, characterized in that, The total mass of the ionic liquid in the composite additive accounts for 0.4%-0.6% of the total mass of the electrolyte, and the total mass of the aniline with branched hydrocarbon substituents accounts for 0.15%-0.25% of the total mass of the electrolyte.

32. An electrolyte having the composite additive according to any one of claims 1-18.

33. A battery having the composite additive according to any one of claims 1-18.

34. An electrochemical device having the composite additive according to any one of claims 1-18.

35. The battery according to claim 33, characterized in that, The battery includes a lithium cobalt oxide battery, which has a capacity retention rate of not less than 70% after 200 cycles at a working voltage of not less than 4.3V, and a discharge specific capacity of not less than 175mAh / g in the third cycle.

Citation Information

Patent Citations

  • Compound additive and electrochemical device applying compound additive

    CN116364930A

  • Nonaqueous electrolyte solution for battery and nonaqueous electrolyte solution battery equipped with it

    JP2008112681A